Estudo da simetria do campo cristalino sobre o \'NI POT.++\' No \'NI\'\' (\'br\'\'o ind.3\') IND.2\'.6\'H IND.2\'o - Ochi, Jose Alberto (1972)
Estudo da simetria do campo cristalino sobre o \'NI POT.++\' No \'NI\'\' (\'br\'\'o ind.3\') IND.2\'.6\'H IND.2\'o